The association between diet quality index-international and inflammatory markers in Iranian overweight and obese women - Shiraseb, Farideh; Ebrahimi, Sara; Noori, Sahar; Bagheri, Reza; Alvarez-Alvarado, Stacey; Wong, Alexei; Mirzaei, Khadijeh (Frontiers in Nutrition, 2023)
Objectives The present study was conducted to evaluate whether there is a link between the diet quality index (DQI) and markers of systemic inflammation in Iranian overweight and obese women. Methods This cross-sectional study included 200 Iranian overweight and obese women aged 18–48 years. The DQI-international (DQI-I) comprises four main components: variety, adequacy, moderation, and overall balance. Blood samples were collected in a fasted state to measure inflammatory markers. Results After adjusting for age, body mass index (BMI), physical activity, total energy intake, economic status, education, supplement intake, age of starting obesity, and history of body mass loss, a marginally significant negative association was observed between the homeostasis model assessment of insulin resistance (HOMA–IR) and the DQI–I (β: −0.015, 95% CI: −0.03, 0.000; p = 0.061). The results after adjustment showed that DQI–I has a negative association with high-sensitivity C-reactive protein (hs–CRP) concentrations (β: −0.031, 95% CI: −0.104, −0.031; p = 0.023). Furthermore, negative associations were observed between the adequacy component and levels of HOMA–IR (β: −0.025, 95% CI: −0.100, 0.047, p = 0.050) and hs-CRP (β: −0.615, 95% CI: −1.191, −0.020; p = 0.045). In addition, negative associations were found between transforming growth factor-β (TGF-β) and balance score (β: −6.270, 95% CI: −39.211, −3.661, p = 0.020), as well as HOMA–IR (β: −0.080, 95% CI: −0.202, −0.000, p = 0.041) and chemoattractant protein−1 (MCP−1) (β: −0.562, 95% CI: −11.414, −0.282, p = 0.021), with the various component. A marginally significant negative association between galectin 3 (Gal-3) and moderation score (β: −0.451, 95% CI: −1.171, 0.060, p = 0.060) was found. In addition, a marginally significant inverse association was also established between hs–CRP and variety score (β: −0.311, 95% CI: −0.970, 0.001, p = 0.052). The Receiver Operating characteristic (ROC) curve analysis demonstrated that DQI–I might better predict HOMA–IR with a cut point of 3.13 (AUC = 0.698, 0.511–0.699, p = 0.050). Conclusion These findings showed that a higher adherence to diet quality and its components could probably be related to lowering the inflammatory markers considerably in overweight and obese women.